Penerapan Sistem Informasi Akuntansi Untuk Persediaan Barang Dagang - Ariqoh Salma Arandhea; Ratih Puspitasari (Jurnal Aplikasi Bisnis Kesatuan, 2021)
Accounting information systems for every company of course have a purpose. Basically the accounting information system is to facilitate the process of existing activities within the company through the provision of appropriate and timely information, as well as creating internal controls to secure the company's assets. The purpose of this study was to determine the application of accounting information systems for merchandise inventory at PT. Padma Sari Pangan by carrying out the activities of receiving goods, purchasing goods, and selling goods that are resold without changing the shape of the goods with inventory activities at retail as an intermediary for distribution channels. Internal control is also needed in the application of accounting information systems at PT. Padma Sari Pangan so that there is no loss or theft of stock items. The results showed that PT. Padma Sari Pangan has an adequate inventory accounting information system so that it plays a role in receiving, buying, and selling goods for distribution activities and internal control of merchandise inventory. Therefore it can be concluded that the application of accounting information systems at PT. Padma Sari Pangan has been accurate in carrying out merchandise distribution activities. keywords : Inventory Accounting Information System, Internal Control